Local Apparatus Professionalism in Realizing Public Service Innovation at Lingga Regency - Alias Alias (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This research was conducted in Lingga Regency using qualitative research methods,and with informants as many as 107 people consisting of; people who are dealing withservice providers, community leaders, entrepreneurs and important people in theadministration of government in Lingga Regency. This research explores dimensionssuch as; structuring the human resources system of the Regional Governmentapparatus, HR competencies of the Regional Government Apparatus, Strengtheningthe Supervision System in the administration of public services, strengthening theapparatus performance accountability, Operational Accountability in the ASNProfessionalism Perspective Before and After Reformation in Lingga Regency, FactorsThat Role Towards Accountability Implementation public service delivery, Factors thathamper Accountability of public service delivery, Performance of Public Service Unitsin Lingga Regency. The results showed that the structuring of the human resourcessystem of the Regional Government apparatus, the competency of the HR of theRegional Government Apparatus, Strengthening the Supervision System, strengtheningthe apparatus performance accountability, Operational Accountability Before andAfter the Reformation had improved, but still needed to be improved to meet the hopesand or desires of the Regency community Phallus.